The Regional Health Sovereignty Performance at the External Border Islands in Republic of Indonesia - Hasim As'ari (Publik : (Jurnal Ilmu Administrasi), 2018)
The purpose of this study is to distinguish the organizational structure performance of the Natuna District Health Office as a regional government organization that carries out the health sector authority in border areas or outermost islands in Indonesia. The research used descriptive method in a qualitative approach and involved 12 informants which were analyzed in depth so as to explain the exact performance of the organizational structure. The results of the study explain that as an area that faces pressure from problems that are different from other regions in Indonesia, Natuna regency always allocates the good financial resources. However, the organizational structure performance which describes the organization and also the management still requires serious attention and continuous improvement efforts.